Aspek Sosial Budaya dan Pengetahuan Ibu Hamil Tentang Mitos Terkait Kehamilan di Desa Mojosarirejo, Kecamatan Driyorejo, Kabupaten Gresik - Fifi Novitasari; Nurul Fitriyah (Universitas Airlangga, 2019)
Pregnancy is a thing that cannot be separated from myths, especially in a developing country like Indonesia. There are cultural traditions in Indonesia, especially those related to myths which are still populer in the society and are not accordance with the health principles which eventually will affect the wellbeings of pregnant women and the fetuses. In Mojosarirejo, there are still many pregnant women who believe in myths and their parents’ superstitious suggestions about pregnancy. The purpose of this study is to find out the knowledge of pregnant woman about pregnancy related myths in the village of Mojosarirejo, the District of Driyorejo, Gresik Regency. This research falls into the category of a descriptive study. 25 pregnant women were taken as the sample. The results of the study showed that there were still many social aspects related to personal support coming from husbands (80%) and advice from parents during pregnancy (96%). Meanwhile, there were also many pregnant women who still believed on the cultural aspects of avoiding certain foods or doing certain behaviors. It was also revealed that only 68% of these pregnant women who knew that certain pregnant-related behaviors were merely myths.